Correction Factors of Interacting Gaseous Systems: A Molecular Approach - P.S., Hari (Asian Journal of Chemistry, 2010)
The formulation of equation of state for a classical chemically interacting gaseous system by incorporating correction factors to ideal volume and pressure is reported. The probabilistic consideration of the average inter molecular separation has provided a helpful method of evaluating the correction factor to the volume of an imperfect gas. A physical interpretation of the van der Waals constant, ‘a' has been made possible through a completely theoretical basis arriving from the results of F. London's dispersion forces.